Correlation of mucocutaneous manifestations of HIV-infected patients in an ART center with CD4 counts - Sonal Lahoti; Kavita Rao; H S Umadevi; Lakshmi Mishra (Wolters Kluwer Medknow Publications, 2017)
Background: As the search for reliable clinical indicators for management of human immunodeficiency virus/AIDS continues, mucocutaneous manifestations of HIV are considered among key clinical indicators for prediction of underlying degree of immunosuppression, systemic opportunistic infections, and disease progression. Objectives: (1) To study the prevalence of mucocutaneous manifestations in HIV-seropositive patients attending the ART center of our hospital (2) To correlate mucocutaneous manifestations with CD4 cell counts. Materials and Methods: A total of 200 HIV-seropositive patients of adult age group visiting our hospital were included in the study. Information on demographics such as age, sex, transmission route, socioeconomic status, educational status, CD4 counts, and mucocutaneous findings was collected through interview administered survey and case records followed by oral and cutaneous examination. Results: Mean CD4 cell count of asymptomatic HIV/AIDS patients was 580.96 cells/mm3. In comparison with the CD4 cell count of asymptomatic HIV-positive patients, (mean 580.96 cells/mm3) CD4 cell count of HIV-positive patients with various mucocutaneous manifestations (mean 409.65 cells/mm3) was correlated using student t-test and was statistically significant (P = 0.017). Conclusion: This study revealed maximum mucocutaneous lesions in the CD4 count range of 200-500. Nail changes accounted for the most common cutaneous manifestation with 53%, and pigmentation accounted for the most common oral manifestation with 39%. Mucocutaneous manifestations can arouse one to suspect the diagnosis of HIV infection in an otherwise healthy unwary patient. They can serve as a dependable marker of HIV disease.